2021
DOI: 10.1039/d1bm01251g
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal delivery of phenytoin-loaded nanoparticles to the brain suppresses pentylenetetrazol-induced generalized tonic clonic seizures in an epilepsy mouse model

Abstract: In this work we describe the preparation and characterization of lecithin-chitosan nanoparticles (L10Ci+), and investigate their ability to deliver the anti-epileptic drug phenytoin (PHT) to mouse brain following intranasal (IN)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…The duration of seizure stages and the total number of EEG signals per stage using equivalent doses of PHT over 1, 4, and 48 h (right). [ 89 ] Copyright 2021, The Royal Society of Chemistry. d) 3D printing of gummy drug formulations composed of gelatin and an HPMC‐based hydrogel for pediatric use.…”
Section: Bioinorganic Materials For Epilepsy Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of seizure stages and the total number of EEG signals per stage using equivalent doses of PHT over 1, 4, and 48 h (right). [ 89 ] Copyright 2021, The Royal Society of Chemistry. d) 3D printing of gummy drug formulations composed of gelatin and an HPMC‐based hydrogel for pediatric use.…”
Section: Bioinorganic Materials For Epilepsy Treatmentmentioning
confidence: 99%
“…Kafa et al utilized PHT‐loaded lecithin‐chitosan (L 10 C i + ) NPs to inhibit generalized tonic‐clonic seizures through IN administration. [ 89 ] The positive charge on the surface of NPs facilitated strong interaction with negatively charged nasal mucosa. The presence of abundant alcohol groups in the chitosan network promoted surface wetting, polymer dispersion, and enhanced PHT release.…”
Section: Bioinorganic Materials For Epilepsy Treatmentmentioning
confidence: 99%
“…The mouse model study demonstrated the potential of lecithin-chitosan nanoparticles (L10Ci+) as a non-invasive phenytoin (PHT) delivery method. This strategy shows the promise of nanomedicine in the treatment of epilepsy by enabling the effective management of the condition with lower doses of PHT [116].…”
Section: Clinical Studies and Patents Of Nanoformulationsmentioning
confidence: 99%
“…developed another sort of NPs, based on chitosan loaded with phenytoin for epilepsy treatment, enabling an extraordinarily rapid time (< 5 min) for brain targeting drug administration via IN delivery. [ 138 ]…”
Section: Therapeutic Applications Of Modified Nps For Brain Diseasesmentioning
confidence: 99%
“…[137] In 2021, Yousfan et al developed another sort of NPs, based on chitosan loaded with phenytoin for epilepsy treatment, enabling an extraordinarily rapid time (< 5 min) for brain targeting drug administration via IN delivery. [138] The CUR-CS-PLGA-NPs are considered to be more effective in delivering curcumin to the brain via IN for the AD treatment, because these NPs possess excellent physiological stability (95%).…”
Section: Chitosan-modified Npsmentioning
confidence: 99%